فاعلية الإدارة الإلكترونية في انماء الموارد البشرية بالمؤسسات الرياضية (دراسة ميدانية لمديرية الشباب والرياضة بالمسيلة) - حجاب, عبدالكريم; عمارة, محمد; د.شريف, حمزة (My University, 2021)
- عنوان الدراسة : فاعلية الإدارة الإلكترونية في انماء الموارد البشرية بالمؤسسات الرياضية (دراسة ميدانية لمديرية الشباب والرياضة بالمسيلة) - أهداف الدراسة :  الوصول إلى معرفة إذا كان استخدام الأجهزة والمعدات يساهم في إنماء الموارد البشرية في المؤسسات الرياضية.  الوصول إلى معرفة إذا كان استخدام البرمجيات يساهم في إنماء الموارد البشرية في المؤسسات الرياضية.  الوصول إلى معرفة إذا كان استخدام شبكات الاتصال يساهم في إنماء الموارد البشرية في المؤسسات الرياضية. - منهج الدراسة: استخدم المنهج الوصفي لملاءمته موضوع الدراسة - مجتمع وعينة الدراسة: تكون المجتمع من عشرين (20) موظفا بمديرية الشباب والرياضة لولاية المسيلة. - أساليب جمع البيانات: الاستبيان والمتمثل في الاستمارة وهو أداة من أدوات الحصول على الحقائق وجمع البيانات والمعلومات - نتائج الدراسة:  أكدت نتائج الدراسة أن عينة الدراسة لها وعي اتجاه ضرورة الانتقال إلى الإدارة الإلكترونية؛  بينت نتائج الدراسة أن الإدارة الإلكترونية تتيح للعاملين فرصة الإبداع وطرح أفكارهم أثناء عملهم من خلال استخدام الأجهزة والمعدات ما انعكس بالإيجاب على تنمية قدراتهم؛  ساهمت الإدارة الإلكترونية في زيادة مهارات وأداء وظائفهم بشكل جيد والتقليل من فرص أخطائهم؛  استخدام عناصر الإدارة الإلكترونية يساهم في تقديم خدمة متميزة للعملاء.  أظهرت نتائج الدراسة أن راض عن مستوى البنية التحتية التقنية والشبكية في إدارة؛  أظهرت النتائج أن أغلبية عينة الدراسة تمتلك المعارف العلمية التي تجعلك تتحكم في تكنولوجيا الاتصال الحديثة؛  رغم التطور التكنولوجيا وتسهيلها للعمل الإداري إلا أنه أغلبية عينة الدراسة معارضون في تعويض خيراتك المهنية القديمة بالخبرة التكنولوجية الحديثة؛  تجعل الإدارة الإلكترونية العاملين يتحكمون في عملهم بشكل أفضل من الإدارة التقليدية  استخدام البرمجيات يساهم في زيادة فعاليتك  أظهرت نتائج الدراسة على أن عينة الدراسة راضية عن مستوى البنية التحتية التقنية والشبكية في الإدارة؛  أكدت أغلبية عينة أنهم راضون على مستوى عن مستوى البنية التحتية التقنية والشبكية في بالإدارة ويرغبون في التخلي عن أساليبهم القديمة في العمل  نظرا لزيادة الوعي وتعلم المورد البشري للتكنولوجيا يسهل عليهم فهم آليات عمل نظام الإدارة الإلكترونية؛  ساهم استخدام شبكات الاتصال يساهم في تقليل الجهد وربح الوقت للموارد البشرية داخل المؤسسة؛ The title of the study is : The Effectiveness of Electronic Management in the Development of Human Resources in Sports Institutions (Field Study of the Directorate of Youth and Sports by Liquefaction). - The objectives of the study:  To find out whether the use of appliances and equipment contributes to the development of human resources in sports institutions.  To find out whether the use of software contributes to the development of human resources in sports institutions.  To find out whether the use of communication networks contributes to the development of human resources in sports institutions. - Curriculum of study: The descriptive approach was used to suit the subject of the study. Society and Study Sample: The community shall be composed of 20 (20) employees of the Directorate of Youth and Sports of the State of Al Masif. - Data collection methods: The questionnaire is a tool for obtaining facts, collecting data and information. - Results of the study:  The results of the study confirmed that the sample study was aware of the need to move to e-governance;  The results of the study showed that e-management provides workers with the opportunity to innovate and put forward their ideas in the course of their work through the use of devices and equipment, which has been positively reflected in the development of their capabilities;  E-management has contributed to increasing their skills and functioning well and reducing their chances of mistakes;  The use of e-management components contributes to a distinct service for clients.  The results of the study showed satisfaction with the level of technical and network infrastructure in management;  The results showed that the majority of the sample of the study had the scientific knowledge to control modern communication technology;  Although technology has evolved and facilitated administrative work, the majority of students are opposed to making up for your old career choices with modern technological experience;  E-management makes people work better than traditional management  Using software contributes to your effectiveness  The results of the study showed that the sample study was satisfied with the level of technical and network infrastructure in the Department;  A majority of the sample confirmed that they were satisfied with the level of technical and network infrastructure in the Department and wished to abandon their old working methods.  Given the increased awareness and learning of the human resource of technology, it is easier for them to understand the working mechanisms of e-governance;  The use of communication networks has contributed to reduced effort and time gain for human resources within the organization;
Keywords: الادارة الالكترونية; الموارد البشرية; المؤسسات الرياضية